Fenofibrate Characterization of Solid Lipid Nanoparticles Using the High Shear Homogenization Method - Muhimmatul Khoiriyah; Jason Merari Perangirangin; Ilham Kuncahyo (HM Publisher, 2022)
Fenofibrate is a drug that can be used to treat hyperlipidemia where the drug is included in the category of Biopharmaceutical classification system II with poor solubility and high permeability. This causes the need to improve the drug delivery system (DDS) made using the solid lipid nanoparticle (SLN) method. SLN fenofibrate can be made using the high shear homogenization method by determining the formula using Factorial 22 Design Expert 12. The formula is made with a concentration of 0.31-1.25% GMS and 1.25-2% Tween-40, then SLN fenofibrate is made by mixing all ingredients until an emulsion is formed and continued with the SLN critical parameter test. From the test results, the critical parameters of SLN fenofibrate for the particle size of 8 formulas 490; 561; 601; 697; 916; 1040; 1818, and 2410 nm. The results obtained for the polydispersity index, respectively, were 0.02; 0.04; 0.08; 0.30; 0.35; 0.48; 0.51, and 0.65. The zeta potential value of the 8 formulas obtained successive values of 2.8; 3.5; 4.2; 4.8; 5.5; 5.8; 8.1, and 8.8 mV. Calculation of the efficiency of the SLN fenofibrate drug obtained successive values of 77.23; 78.53; 79.51; 80.47; 81.17; 87.38; 87.39, and 87.82%. The SLN method can improve drugs that are included in the Biopharmaceutical classification system class II category with the distribution of test results in the particle size range, and the adsorbed drug is more than 70%.